Advancing education through e-learning innovation: the case of the Crocodile Chemistry program in higher education - Alqallaf, Nawal; Almahmeed, Zahra; Alsaber, Ahmad; Alboloushi, Bedour; Alkandari, Anwaar; Alhashem, Fatimah (Frontiers in Education, 2025)
IntroductionE-learning innovations have transformed higher education, particularly in STEM fields like chemistry. Traditional laboratory instruction faces limitations such as high costs, safety concerns, and accessibility issues. Virtual laboratories provide scalable alternatives to enhance student engagement and comprehension. This study evaluates the effectiveness of the Crocodile Chemistry program in improving students’ understanding of chemical concepts, academic performance, and motivation at the Public Authority for Applied Education and Training (PAAET).MethodsA quasi-experimental design compared an experimental group (n = 102) using Crocodile Chemistry with a control group (n = 103) following traditional laboratory instruction. Pre-test and post-test assessments were conducted using the Alternative Chemical Concepts Test. Paired t-tests measured performance changes, and correlation analysis assessed learning consistency. The Partial Credit Model (PCM) evaluated test reliability and instructional effectiveness.ResultsPaired t-tests revealed significant performance improvements for the experimental group (p < 0.05), whereas the control group showed minimal changes. PCM analysis demonstrated higher reliability for the experimental group (0.774) compared to the control (0.403), indicating better differentiation of student abilities. Correlation analysis showed a strong relationship between pre- and post-test scores (r = −0.795, p < 0.001), confirming the program’s role in enhancing learning outcomes.DiscussionThe findings highlight the potential of virtual laboratories to modernize chemistry education by improving comprehension, engagement, and academic performance. This study supports the integration of digital tools in higher education to enhance learning outcomes and student motivation.